Crystal structure and temperature-dependent luminescence of a heterotetranuclear sodium-europium(III) beta-diketonate complex - Bruno, Sofia M.
A heterotetranuclear Na2Eu2 complex with uncommon photo-luminescence properties is reported. The complex exhibits good emission efficiency at ambient temperature, coupled with strong temperature dependence of the emission intensity and lifetime in the 273-333 K range, all of which are key features for non-contact luminescence-based thermometers capable of sensing and imaging temperatures in the physiological range.